2013
DOI: 10.1152/ajpregu.00377.2012
|View full text |Cite
|
Sign up to set email alerts
|

Leptin receptor antagonist treatment ameliorates the effects of long-term maternal hypoxia on adrenal expression of key steroidogenic genes in the ovine fetus

Abstract: We previously reported elevated adipose leptin expression, plasma leptin concentrations, and adrenocortical leptin receptor expression in the long-term hypoxic (LTH) ovine fetus. This study addressed whether leptin antagonist (LA) administration to LTH fetal sheep altered expression of key genes governing cortisol synthesis. Ewes were maintained at high altitude (3,820 meters) from 40 to 130 days gestation (dG), returned to Loma Linda University, and implanted with a maternal tracheal catheter. Reduced Po2 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In a recent review, it was also clearly shown that leptin antagonism therapy works for the prevention and treatment of immunity-related disorder in mice [82]. It has been shown that LR antagonists abrogate the effects of long-term maternal hypoxia by governing the key enzyme StAR, and other factors play a role in modulating cortisol synthesis in these fetuses [83]. As mentioned above, leptin mediates several physiological functions, such as regulation of energy metabolism and reproductive function, and induces autoimmune diseases by enhancing immune response, tumorogenesis, elevated blood pressure and cardiovascular pathologies.…”
Section: Leptin In Autoimmune Disease: Its Antagonist As a New Therapmentioning
confidence: 99%
“…In a recent review, it was also clearly shown that leptin antagonism therapy works for the prevention and treatment of immunity-related disorder in mice [82]. It has been shown that LR antagonists abrogate the effects of long-term maternal hypoxia by governing the key enzyme StAR, and other factors play a role in modulating cortisol synthesis in these fetuses [83]. As mentioned above, leptin mediates several physiological functions, such as regulation of energy metabolism and reproductive function, and induces autoimmune diseases by enhancing immune response, tumorogenesis, elevated blood pressure and cardiovascular pathologies.…”
Section: Leptin In Autoimmune Disease: Its Antagonist As a New Therapmentioning
confidence: 99%
“…The leptin mutant competes with endogenous leptin for binding sites on all forms of the leptin receptor but lacks biological activity (34). In fetal sheep, a less potent form of the recombinant ovine leptin receptor antagonist (mutant L39A/D40A/FA1A/I42A, OLA) at a dose of 1.5 mg•kg Ϫ1 •day Ϫ1 iv has previously been shown to reduce STAT-3 phosphorylation by~50% in the adrenal cortex (11). The treatments were administered via the fetal venous catheter at a rate of 3 ml/day using a Graseby portable infusion pump.…”
Section: Methodsmentioning
confidence: 99%
“…Upon arrival at Loma Linda University Medical Center Animal Research Facility (elevation: 346 m), arterial and nonocclusive tracheal catheters were surgically placed as we previously described. [23][24][25] Maternal PO 2 was maintained at *60 mm Hg for the LTH ewes by adjusting the flow of humidified nitrogen (N 2 ) gas through the maternal tracheal catheter. Normoxic control ewes (n ¼ 6) were maintained near sea level (*300 m) throughout gestation.…”
Section: Animalsmentioning
confidence: 99%
“…We have previously published this methodology in our laboratories for NOS isoforms and other proteins. 20,23,25 Locule Size and Distribution…”
Section: Polymerase Chain Reaction Quantification Of Mitochondrial Anmentioning
confidence: 99%
See 1 more Smart Citation